Is Political Science a Science? The Evolution of Popper's Metaphor - Nouha Khelfa; Sayed Mustafa Zamani (Jurnal Politik Indonesia, 2023)
In this literature review, we aim to answer the question, is political science a science? through revisiting the work of Gabriel Almond and Stephen Genco, titled Clouds, clocks, and the study of politics (1977). We will show the paradigm shift in understanding the subject matter of social sciences in terms of epistemology, ontology, and methodology, from the positivist clock-like model to the plastic model of the post- behavioralist schools, relying on the three-stage metamorphosis of Popper’s metaphor of clouds and clocks. Then, we will show how our definition of science has transformed from methodology-focused iron-like rigidity of positivists to the substance-based pursuit of understanding plastic reality. The review fundamentally links the change in the perception of social science as a science to the transformation of our understanding of science as a whole, after the emergence of quantum mechanics and the uncertainty principle of Heisenberg. The end result of this critical review reveals that political science is a science because science itself is not only about regularities and strict laws of classical mechanics, but it is about malleable realities. Therefore, although the subject matter of hard science differs from that of political science, political science could develop on parallel with hard science.